CREATING AN ENGLISH LEARNING 3D GAME (Archive of Conferences, 2021)
This article deals with learning English through games. This article shows how games are highly motivating because they are amusing and interesting. Advantages of games in learning are well-described and types of games are shown clearly in this article.